Superheater deposits and corrosion in temperature gradient – Laboratory studies into effects of flue gas composition, initial deposit structure, and exposure time. (1st August 2021) - Niemi, Jonne; Engblom, Markus; Laurén, Tor; Yrjas, Patrik; Lehmusto, Juho; Hupa, Mikko; Lindberg, Daniel
Abstract: The heterogeneous nature of the ash chemistry of biomass fuels gives rise to challenges in predicting the deposit melting, sintering, and enrichment of corrosive ash species. An experimental method has been developed to study the evolution of ash deposit chemistry and morphology in temperature gradients simulating the conditions of real superheater deposits. The method is based on applying synthetic ash mixtures on an air-cooled corrosion probe, which is inserted into a tube furnace. The focus has been on how the melting behavior of alkali salt-rich deposits, i.e., KCl–K2 SO4 –NaCl–Na2 SO4 mixtures, affects the chemistry and morphology. Intradeposit vaporization-condensation of alkali chlorides has been of interest. The interaction of reactive gas components (H2 O + SO2 ), with the deposits, was also studied. The vaporization-condensation mechanism leads to enrichment of alkali chlorides in crevices and voids within deposits, leading also to build-up of chlorides on the steel surface, which causes accelerated corrosion, due to the formation of low-melting FeCl2 mixtures. Liquid phase sintering and temperature gradient zone melting (TGZM) were the main mechanisms for the supersolidus sintering of the deposits. Iron and nickel oxides were found within the deposits and at the outer edge of deposits, due to the TGZM mechanism. Highlights: Alkali chloride deposits react with gaseous H2 O and SO2 and form alkali sulfates. Alkali chlorides enrich in crevices and cracks in ash deposits. Deposits with fine particles sinter faster and more compared to coarse particles. Corrosion products were observed to migrate to the outer edge of deposits. The corrosion product migration is due to temperature gradient induced diffusion.